Comparative characteristics of the effectiveness of complex therapy in the surgical treatment of acute condyloma of the anogenital region with the use of drugs - nitrogen donors - Slepichko, A.; Deykalo , I. (Journal of Education, Health and Sport, 2021)
The paper presents comparative data on the effectiveness of complex treatment of acute condyloma of the anogenital region (n = 105). Destruction of genital warts was performed surgically, preceded by immunomodulatory and antiviral systemic therapy and local treatment with antiseptic measures and hyaluronic acid, which continued in the postoperative period. Patients of the first group (n = 70) were added to the complex therapy drug - nitrogen donor L - arginine. Efficacy control consisted of subjective assessment and patient complaints; objective determination of the clinical condition, the course of the postoperative period, assessment of the state of microcirculation; laboratory dynamics of interleukin levels; the presence of recurrence of the disease. The use of nitrogen donor (L-arginine) in complex therapy allows to eliminate subjective symptoms, signs of secondary bacterial contamination in the preoperative period, postoperative pain, post-traumatic stress and to provide a significantly higher rate of epithelization, which optimizes the patient's stay. prognosis for recurrence of AW. The obtained results showed a significantly higher efficiency of complex treatment of acute genital warts of the anogenital region in the group of patients receiving a nitrogen donor L - arginine. In the group of patients receiving L-arginine (n = 70), there were 2 (2,86 %) relapses. In the control (n = 35) group – 3 (8,57 %) (p < 0.05).